2007
DOI: 10.1111/j.1524-475x.2007.00239.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of gaseous nitric oxide in the treatment of skin and soft tissue infections

Abstract: Bacterial burden significantly interferes with the healing process in chronic ulcers. Nitric oxide (NO) plays a key role in regulating skin's response to infection and wound healing. In previous studies, we demonstrated that exogenous NO gas (gNO) at 200 parts per million (ppm) exhibits potent antimicrobial effects against a representative range of pathogens. The aim of the present study is to explore the antimicrobial properties of gNO in vivo and to determine skin cells' sensitivity to the cytotoxic effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
46
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 64 publications
(138 reference statements)
7
46
0
1
Order By: Relevance
“…Here we provide evidence that 160 ppm NO, a concentration previously identified as an effective antimicrobial dose against various microorganisms in vitro, ex vivo and in animal models [16,17,19], can be safely delivered to healthy human lungs in a pulsed manner for 5 consecutive days. No significant adverse events occurred and only three minor adverse events, not attributable to NO, were reported.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Here we provide evidence that 160 ppm NO, a concentration previously identified as an effective antimicrobial dose against various microorganisms in vitro, ex vivo and in animal models [16,17,19], can be safely delivered to healthy human lungs in a pulsed manner for 5 consecutive days. No significant adverse events occurred and only three minor adverse events, not attributable to NO, were reported.…”
Section: Discussionmentioning
confidence: 94%
“…At 160-200 ppm, NO has also been shown in vitro, ex vivo and in animal models [14][15][16][17][18][19][20] to exert potent antimicrobial effects against a broad range of microbes, suggesting its use in appropriate concentrations in CF patients. At present, however, inhalation of NO as a selective, short acting vasodilator is approved only at 80 ppm for use in full term infants with hypoxic respiratory failure associated with pulmonary hypertension [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Not only is NO antimicrobial at concentrations of 200 ppm but also it has been shown to improve the healing of burns. 19,20 In addition to its direct activity as an antimicrobial, NO has been implicated in gene regulation. We sought to identify NO-regulated molecules that could affect the host response to infectious agents.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Ghaffari et al [284] exogenous NO in gaseous state was directly administered to puncture wounds without any carriers in which the treatment achieved significant reduction in inoculated S. aureus numbers. It was also reported that gaseous NO (gNO) treatment did not cause any cytotoxic effects to skin cells tested such as fibroblasts and keratinocytes and thus did not hinder the wound healing process [284]. A topical formulation comprising gNO carriers has been patented by Av-Gay et al [285] which are capable of releasing therapeutically effective amounts of the gas when applied to a wound.…”
Section: Nitric Oxide Generatorsmentioning
confidence: 99%